Alstroemeriaceae endémicas del Perú - León, Blanca (2006)
Mostly herbs and vines, the Alstroemeriaceae are represented in Peru with 85 species in two genera, Alstroemeria and Bomarea (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we recognize 22 endemic taxa, all in the genus Bomarea. These endemic taxa occupy several ecological regions, from Humid Montane Forest to the Dry and Humid Puna, between 1000 and 4600 m elevation. Approximately a third of the species are known only from their type localities, located in isolated mountain ranges o in basins that had received scarce attention from botanists over the last 80 years, as in the case of the Monzón. Nine of these species have been recorded in Peru’s protected areas network.